Optimizing the role of health cadres in blood pressure monitoring in Kindingan Village, Hulu Sungai Tengah Regency - Saputri, Rina; Basit, Mohammad; Hidayat, Ahmad; Hakim, Ali Rakhman; Anisa, Fadhiyah Noor (Community Empowerment, 2025)
This community service aims to enhance the capacity of health cadres in Kindingan Village in blood pressure measurement using digital sphygmomanometers. The main problems faced by the service partners are the cadres' low understanding of sphygmomanometer usage, normal blood pressure limits, and pulse monitoring. This activity was conducted in several stages, namely theoretical training, practical training, and evaluation. The team provided grants in the form of 10 units of digital sphygmomanometers and 5 units of infant and adult weighing scales to support their role in community health monitoring. The training results showed a significant increase in the cadres' understanding and skills in accurately measuring blood pressure. The cadres are now able to understand normal blood pressure limits and utilize the pulse feature on the sphygmomanometers, and it is expected that this will improve the overall quality of community health monitoring, especially in the early detection of hypertension.